A review on membraneless laminar flow-based fuel cells - Shaegh, Seyed Ali Mousavi (2012)
The review article provides a methodical approach for understanding membranelesslaminarflow-basedfuelcells (LFFCs), also known as microfluidic fuelcells. Membraneless LFFCs benefit from the lamination of multiple streams in a microchannel. The lack of convective mixing leads to a well-defined liquid–liquid interface. Usually, anode and cathode are positioned at both sides of the interface. The liquid–liquid interface is considered as a virtual membrane and ions can travel across the channel to reach the other side and complete the ionic conduction. The advantage of membraneless LFFC is the lack of a physical membrane and the related issues of membrane conditioning can be eliminated or becomes less important. Based on the electrode architectures, membraneless LFFCs in the literature can be categorized into three main types: flow-over design with planar electrodes, flow-through design with three-dimensional porous electrodes, and membraneless LFFCs with air-breathing cathode. Since this paper focuses on reviewing the design considerations of membraneless LFFCs, a concept map is provided for understanding the cross-related problems. The impacts of flow and electrode architecture on cell performance and fuel utilization are discussed. In addition, the main challenges and key issues for further development of membraneless LFFCs are discussed.